2003
DOI: 10.1023/b:hijo.0000023384.02037.bb
|View full text |Cite
|
Sign up to set email alerts
|

Lectin Histochemistry of Normal Human Lung

Abstract: This study aimed to identify and specify the glycotypes of cell populations in normal human lung including types I and II pneumocytes, alveolar macrophages and mast cells, and also in the larger tissue structures of lung, including blood vessels and bronchi/bronchioles, using lectin- and immuno-histochemistry on paraffin-embedded tissue from 11 normal cases. The alveolar macrophages were anti-CD68 positive whereas the cells lining the alveolar walls were positive for cytokeratins. The alveolar macrophages in n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 23 publications
2
15
0
Order By: Relevance
“…We did not find references about lectin binding pattern in intestine or lung from bovine foetuses without infectious cause of abortion. In one study, Barkhordari et al. (2004) revealed that in human lung most of the lectins (Con A, UEA‐I, DBA y SBA) did not react with vascular endothelium as we noted in the vascular endothelium of all bovine foetuses.…”
Section: Discussionsupporting
confidence: 47%
“…We did not find references about lectin binding pattern in intestine or lung from bovine foetuses without infectious cause of abortion. In one study, Barkhordari et al. (2004) revealed that in human lung most of the lectins (Con A, UEA‐I, DBA y SBA) did not react with vascular endothelium as we noted in the vascular endothelium of all bovine foetuses.…”
Section: Discussionsupporting
confidence: 47%
“…Many high and low pathogenic influenza virus infections of domestic and live bird market poultry have been found to infect lungs and viral antigen has been demonstrated in lungs tissues [26,27]. The presence of lung infection in conjunction with failure to detect receptors might indicate that the distribution of receptors in the respiratory tract might not be as clear cut as we observe using lectin histochemistry and that other host and viral components might play a role [28,29]. …”
Section: Discussionmentioning
confidence: 88%
“…Lectins which were discovered more than 100 years ago, recently found new application as novel markers of different types and subtypes of cells, e.g. -GNA and N. pseudonarcissus lectins were shown to bind specifically with macrophages, WGA (succinylated) -with type I pneumocytes (Barkhordari et al 2004), Amaranthus leucocarpus lectin -with naive T cells (Porras et al 2000). Besides, different lectins were also used as markers for specific tumour determinants (Wu 2004, Guillot et al 2004 We suggest that biological role of elevated expression of a-d-Man-and b-d-Gal-containing glycoproteins during apoptosis could be important for labeling the apoptotic cell for their next elimination by the macrophages and/or neighbouring epithelial cells.…”
Section: Discussionmentioning
confidence: 99%